CHLH/GUN5 Function in Tetrapyrrole Metabolism Is Correlated with Plastid Signaling but not ABA Responses in Guard Cells - Ibata, Harue; Nagatani, Akira; Mochizuki, Nobuyoshi (Frontiers in Plant Science, 2016)
Expression of Photosynthesis-Associated Nuclear Genes (PhANGs) is controlled by environmental stimuli and plastid-derived signals (“plastid signals”) transmitting the developmental and functional status of plastids to the nucleus. Arabidopsis genomes uncoupled (gun) mutants exhibit defects in plastid signaling, leading to ectopic expression of PhANGs in the absence of chloroplast development. GUN5 encodes the plastid-localized Mg-chelatase enzyme subunit (CHLH), and recent studies suggest that CHLH is a multifunctional protein involved in tetrapyrrole biosynthesis, plastid signaling and ABA responses in guard cells. To understand the basis of CHLH multifunctionality, we investigated fifteen gun5 missense mutant alleles and transgenic lines expressing a series of truncated CHLH proteins in a severe gun5 allele (cch) background (tCHLHs, ten different versions). Here, we show that Mg-chelatase function and plastid signaling are generally correlated; in contrast, based on the analysis of the gun5 missense mutant alleles, ABA-regulated stomatal control is distinct from these two other functions. We found that none of the tCHLHs could restore plastid-signaling or Mg-chelatase functions. Additionally, we found that both the C-terminal half and N-terminal half of CHLH function in ABA-induced stomatal movement.